Effect of camel milk on glucose metabolism in adults with normal glucose tolerance and type 2 diabetes in Raica community: a crossover study - Agrawal, R.P.; Sharma, P.; Gafoorunissa, et al., S.J. (Acta Biomedica Atenei Parmensis, 2012)
Background: To investigate effects of camel milk consumption on insulin sensitivity and glycemic control in normal and type-2 diabetics of Raika and Non-Raika community. Methods: 28 raika and non-raika male were enrolled in study, categorized in 2 groups, non-diabetic and diabetic after one month stabilization. Non-diabetics were supplemented with cow milk and diabetics with camel milk; followed by one-month washout period. Afterwards regimen was interchanged for 3 months. Biochemical and anthropometric data was recorded at baseline, after stabilization, before and after washout and at end of study. Results: An improving trend was observed in both the groups for camel milk effect (FBS 203.86±24.09 to 161.43±11.39 mg/dl;p